THE ROLE OF EDUCATIONAL SUPPORT SYSTEMS IN INTEGRATING ENVIRONMENTAL EDUCATION INTO LIFE SCIENCES - Khathutshelo Ronald Munasi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Integrating Environmental Education into the Life Sciences curriculum is crucial for fostering environmental literacy and promoting sustainable development. This study explores the role of educational support systems—including policy documents, textbooks, and subject advisors—in facilitating Environmental Education (EE) integration in the Vhembe District of South Africa. Guided by Bronfenbrenner’s Ecological Systems Theory, the research adopts a qualitative, phenomenological case study approach, utilizing document analysis and semi-structured interviews with Life Sciences teachers and a subject advisor. The findings reveal significant gaps in the instructional support provided by resources such as the Curriculum and Assessment Policy Statement (CAPS), textbooks, and pacesetters. These foundational materials lack explicit strategies for effective EE integration. Additionally, subject advisors face challenges in offering specialized support due to systemic constraints, including a focus on general curriculum goals and limited resources. This study underscores the urgent need for a cohesive and comprehensive approach to EE integration. Key recommendations include the development of targeted instructional resources, enhanced professional development for educators, and better coordination between policy and implementation. These measures are essential for equipping educators to deliver meaningful Environmental Education, enabling learners to address critical environmental challenges and contribute to sustainable development.